Kawih Ayang-Ayang Gung : Sumber Pembelajaran Etnopedagogik Mata Pelajaran Sosiologi - Hartono, Tio Budi; Wildan, Dadan; Komariah, Siti (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This article explains that all of them are a source of learning in sociology subjects. The purpose of this study is to find out the meaning of kawih ayang-ayang gung which is rich in socio-political mankana, so that it can enrich sociology learning. This research is a descriptive research. The object of research is kawih ayang-ayang gung and ethnopedagogic studies. Data collection is done with library research. Data analysis techniques are carried out by analyzing values in all kinds of people so that they become a source of learning in sociology subjects. This study shows that, (1) kawih ayang-ayang gung is a legacy of folklore traditions passed down in society (2) kawih ayangayang gung contains the meaning of prohibition in a socio-political context. (3) Kawih ayang-ayang gung became a source of learning with culture in sociology subjects.